Tafsir Nusantara: Karakteristik Pemikiran Syekh Nawawi al-Bantanī dalam Tafsir Marāḥ Labīd - Erlan Dwi Cahyo; Hamdan Maghribi; Andri Nirwana AN (KURAS Institute, 2022)
This article aims to look at Shaikh Nawawī al-Bantanī's view in his tafsīr Marāḥ Labīd as a form of his magnum opus among his other works. This article uses a literature review with a content analytical approach to Tafsīr Marāḥ Labīd and other suitable secondary sources to obtain views and facts as well as an analysis of its contents. This article finds that Nawawī al-Bantanī's interpretation of Tafsir Marāḥ Labīd in the socio-historical-political context during the Dutch colonial period made al-Bantanī pay full attention to the problems of the community and nationality. The context of writing Marāḥ Labīd's tafsīr still has quite a strong relevance to the present day, especially in the transformation of values ​​and methods. This article also finds that Marāḥ Labīd's interpretation has the characteristics of language interpretation (linguistics), socio-historical (asbāb al-nuzūl), fiqh, culture, and logical interpretation. It is marked by a holistic-interdisciplinary interpretation of Surah Al-Fatihah which contains three central religious teachings, which include faith, Sufism/morals, and Shari'a. Although Marāḥ Labīd cites many references to classical interpretations, he also provides contextual analysis that relates to his era. From Marāḥ Labīd it was also concluded that al-Bantanī's struggle was not limited to the physical but also through academic transmission.